Josiah the Great : The True Story of the Man Who Would be king - Macintyre, Ben 1963- (London HarperCollins Publishers, 2004)
In the winter of 1838, an adventurer, surrounded by native troops and mounted on an elephant, raised the American flag on the summit of the Hindu Kush in the mountainous wilds of Afghanistan. He declared himself Prince of Ghor, Paramount Chief of the Hazarajat, and the spiritual and military heir to Alexander the Great. His name was Josiah Harlan. A Pennsylvania Quaker, Harlan was the first American ever to enter.
Include Index and Bibliography
Keywords: Afghanistan -- Adventure and adventurers -- Kings and rulers